The Effectiveness of Augmented Reality Based on Assemblr Edu to Increase Learning Interest and Student Learning Outcomes - Lissa'adah, Luthfiyatul; Widiyatmoko, Arif (Universitas Negeri Semarang, 2023)
The purpose of this study is to analyze the effectiveness of Assemblr Edu-based augmented reality in increasing student interest and learning outcomes. The research design used is nonequivalent control group design. The technique that will be used in this study is simple random sampling. The results showed that Assemblr Edu-based augmented reality media is very valid so it is worth using in learning. The learning interest of students measured through questionnaires has increased which is calculated using N-Gain of 0.31 which is included in the moderate category. The learning outcomes of the experimental class learners measured through the reasoned multiple-choice test also addressed an increase calculated using an N-Gain of 0.50 which belongs to the moderate category. The conclusion of this study is that augmented reality media based on Assemblr Edu is effective for increasing students' interest in learning and learning outcomes in human excretion system materials.